“You Should Praise” – “You Should Kill”: The Contingent Negative Variation Indicates Moral Goodness and Badness - Neuhaus, Christiane (Frontiers in Human Neuroscience, 2019)
Moral advice (how to behave in life) is often conveyed by short, simple sentence constructions:: ‘You – should – [plus verb with moral meaning]’. Yet, how moral prescriptions are processed has never been studied from a neurocognitive perspective. The results of this study suggest that the Contingent Negative Variation (CNV) serves a neural correlate for moral (and immoral) predictive phrases. In step one, the original CNV paradigm (‘S1 – S2 – motor response’) was extended using action-demanding three-word phrases taken from everyday contexts (e.g. “Ready – Set – Go”). In step two, these commands were replaced by abstract words, each phrase then including a verb of moral or immoral meaning (e.g., “You should hope”, “You should praise”, “You should lie”). During recording, each phrase type - e.g. moral or immoral - was presented blockwise. The task varied according to block order: Participants (n = 19) either had to listen attentively or respond with a finger tap immediately after the final word of a phrase. EEG data were bandpass filtered (0.1 - 30 Hz) and analyzed at the onset of the second word, yielding two independent responses: a bilateral CNV and a bilateral motor-related negativity, both decreasing from anterior to posterior. The results show that the CNV is sensitive to phrase constructions of moral resp. immoral valence. Thus, transfer to remote semantic fields seems possible. Importantly, this transfer is combined with a change of time frames, from restricted and highly pragmatic (as in the original paradigm) to indefinite and vague. Thus, a CNV may not only indicate preparation to action but also general guidelines for social life. An N400 occurring as an additional, task-dependent result cannot be sufficiently explained on the basis of the present data.